2018
DOI: 10.1371/journal.pone.0198464
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MMP-2 and MMP-9 enzyme activity on wound healing, tumor growth and RACPP cleavage

Abstract: Matrix metalloproteinases-2 and -9 (MMP-2/-9) are key tissue remodeling enzymes that have multiple overlapping activities critical for wound healing and tumor progression in vivo. To overcome issues of redundancy in studying their functions in vivo, we created MMP-2/-9 double knockout (DKO) mice in the C57BL/6 background to examine wound healing. We then bred the DKO mice into the polyomavirus middle T (PyVmT) model of breast cancer to analyze the role of these enzymes in tumorigenesis. Breeding analyses indic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 47 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…In recent years, numerous insightful studies have demonstrated that MMP‐2 is over‐expressed in GBM and has a characteristic ability to recognize and cleave peptides with specific sequences. [ 28,29,35 ] As such, various substrates of MMP‐2 were designed to enhance specificity for drug delivery, thus leading to a remarkable effort toward the investigation of drug‐targeted delivery systems. The present study aimed to conjugate PTX with the effective MMP‐2‐sensitive linker, PVGLIG to reduce off‐target binding and side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, numerous insightful studies have demonstrated that MMP‐2 is over‐expressed in GBM and has a characteristic ability to recognize and cleave peptides with specific sequences. [ 28,29,35 ] As such, various substrates of MMP‐2 were designed to enhance specificity for drug delivery, thus leading to a remarkable effort toward the investigation of drug‐targeted delivery systems. The present study aimed to conjugate PTX with the effective MMP‐2‐sensitive linker, PVGLIG to reduce off‐target binding and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases‐2 (MMP‐2; 72kD), a member of the MMP family, plays multiple roles in the progression of tumors. [ 28,29 ] Compared with almost no expression in normal brain tissue, it has been suggested that MMP‐2 is highly expressed in glioma tissues. [ 30,31 ] Furthermore, mRNA and protein levels of MMP‐2 increase along with the stage of glioma progression, closely associated with the invasion of glioma cells.…”
Section: Introductionmentioning
confidence: 99%
“…The results of immunohistochemical analysis showed that there was signi cant difference in TNM staging between the high in ltration density group and the low in ltration density group in TS (P < 0.05), which indicated that TAM polarization and TS in ltration promoted the malignant progression of breast cancer,. Consistent studies have shown that TAM can secrete a variety of angiogenic factor, such as VEGF, MMP9, tumor necrosis factor (TNF), TGF-β, EGF, broblast growth factor (FGF) to promote angiogenesis (31,32).TAM is transformed into M2 to enhance tumor angiogenesis in advanced tumors (33). In breast cancer, TAM can also secrete matrix metalloproteinase 9 (MMP9) and matrix metalloproteinase 2 (MMP2) to degrade the extracellular matrix, M2 can produce high level of MMP, promote extracellular matrix (ECM) degradation, and stimulate tumorigenesis, cancer cell invasion and metastasis by activating Epithelial-mesenchymal transition (EMT) (31,34).…”
Section: Discussionmentioning
confidence: 99%
“…53 Owing to their special structures, the NPs prepared from mPEG-peptide-PCL exhibit their own characteristics, such as prolonged circulation time and accumulation in the tumor site by the EPR effect. [54][55][56] MMPs are abundantly present in tumors, 57,58 and have been considered as tumorspecific stimuli for cancer imaging and drug delivery. 59,60 Following the accumulation of NPs in the tumors, the mPEG-peptide-PCL conjugates will be cleaved at a certain site of the MMP2/9 peptide by MMP2/9.…”
Section: Discussionmentioning
confidence: 99%